Error Analysis of English by 8-th Grade Students at SMPN 4 Baturiti - Gusti Ngurah Surya Permadi Pinatih Sargunawan; I Nyoman Aryawibawa; I Nyoman Udayana (CV. Ulil Albab Corp, 2023)
Thesis with the title Error Analysis of English by 8th-grade student in SMPN 4 Baturiti. This thesis aims to analyze the repeated errors made by SMPN 4 Baturiti students to find the types of errors in their writing, the causes of students in error writing, Writing in English is not easy even though the students have learned this before. They still find some problems in writing and cannot write the sentences in right structure. They still need more knowledge to understand the basics. The students still write sentences by using Indonesian rules and also still miss in grammar knowledge. The data used in the study was taken from descriptive writing test by the students in SMPN 4 Baturiti, Tabanan. The eight grade student was chosen because they already know how to make a descriptive text and they have learned it before. This school has four classes of eighth-grade (8A-8D). In this study, the writing data were taken from students in 8B. In collecting data, this thesis uses qualitative methods. In collecting data there are four steps used, namely first, selecting data properly, identifying errors, then classifying data based on its type, and finally evaluating the data found. In analyzing the data, the theory of error analysis was used by Ellis (1997). The results of the analysis show the types of errors found in the writing of SMPN 4 Baturiti students. Errors found in youth writing are grouped and categorized into four types: Omission. There are five omission errors. These errors were found and analyzed with a syntactic structure perspective.